2019
DOI: 10.1016/j.snb.2018.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Au decorated core-shell structured Au@Pt for the glucose oxidation reaction

Abstract: Highlights  • Bimetallic Au@Pt nanoparticles as core-shell structures demonstrate the enhanced catalytic performance for glucose oxidation.  • Nafion layer and dendritic Pt shells prevent passivation of the Au core and additional Au plating further enhances catalytic performance.  • Rationally designed Au-decorated Au@Pt NPs show enhanced sensitivity, stability, and selectivity towards glucose detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…Among the oxidoreductase nanozymes, peroxidase-and oxidase-mimicking nanomaterials are mostly explored for electrochemical biosensors (Table 1). The common nanomaterials with peroxidase mimetics includes metal nanoparticles (AuNPs, 50 PdNPs 51 ), metal oxides (Fe2O3, 52,53 Au-NPFe2O3NC, 54,55 Fe3O4 MNP, 56 CeO2/NiO, 57 and CuO 58 ), core-shell nanostructure(Au@Pt 59 ), dendrite (dealloyed-AuNi@pTBA, 60 Cu-Co alloy dendrite 61 ), carbonbased composite(GO-AuNP, 62 His@AuNCs/rGO, 63 PtNPs decorated CNT 64 ), and metal-organic frameworks (MOFs). Unlike other nanomaterials, MOFs have drawn enormous interest as a new class of nanozymes due to their uniform cavities which are likely to provide biomimetic active centers and enzyme-like pseudo-substrate-binding pockets.…”
Section: Common Nanozymes For Electrochemical Biosensorsmentioning
confidence: 99%
“…Among the oxidoreductase nanozymes, peroxidase-and oxidase-mimicking nanomaterials are mostly explored for electrochemical biosensors (Table 1). The common nanomaterials with peroxidase mimetics includes metal nanoparticles (AuNPs, 50 PdNPs 51 ), metal oxides (Fe2O3, 52,53 Au-NPFe2O3NC, 54,55 Fe3O4 MNP, 56 CeO2/NiO, 57 and CuO 58 ), core-shell nanostructure(Au@Pt 59 ), dendrite (dealloyed-AuNi@pTBA, 60 Cu-Co alloy dendrite 61 ), carbonbased composite(GO-AuNP, 62 His@AuNCs/rGO, 63 PtNPs decorated CNT 64 ), and metal-organic frameworks (MOFs). Unlike other nanomaterials, MOFs have drawn enormous interest as a new class of nanozymes due to their uniform cavities which are likely to provide biomimetic active centers and enzyme-like pseudo-substrate-binding pockets.…”
Section: Common Nanozymes For Electrochemical Biosensorsmentioning
confidence: 99%
“…In particular, the catalytic efficiency can be easily improved through a large surface-to-volume ratio. In addition to these methods, composition changes to partially replace the Pt by the addition of carbon and/or metals (Fe, Co, Ni, Pd, Au, and Ag) have also been accelerated for greater catalytic activity and durability 1018 .…”
Section: Introductionmentioning
confidence: 99%
“…The surface Pt-rich bimetallic nanocatalysts with different Au/Pt atomic ratios have demonstrated enhanced hydrogenation selectivity or activity than AuPt alloys and monometallic Pt nanomaterials [20,21]. In addition, Au@Pt NPs showed the highest response current for the catalytic oxidation of glucose solution compared with those of Pt and Au NPs [22,23]. Recent theoretical predictions showed that the PtAu surface avoids the CO formation and apparently exhibits higher CO-poisoning tolerance when compared with the Pt@Pd surface [24].…”
Section: Introductionmentioning
confidence: 99%